Nature-derived microbiota exposure as a novel immunomodulatory approach. (17th May 2018) - Nurminen, Noora; Lin, Jake; Grönroos, Mira; Puhakka, Riikka; Kramna, Lenka; Vari, Heli K; Viskari, Hanna; Oikarinen, Sami; Roslund, Marja; Parajuli, Anirudra; Tyni, Iiris; Cinek, Ondrej; et al.
Aim: Current attempts to modulate the human microbiota and immune responses are based on probiotics or human-derived bacterial transplants. We investigated microbial modulation by soil and plant-based material.Materials & methods: We performed a pilot study in which healthy adults were exposed to the varied microbial community of a soil- and plant-based material.Results: The method was safe and feasible; exposure was associated with an increase in gut microbial diversity.Conclusion: If these findings are reproduced in larger studies nature-derived microbial exposure strategies could be further developed for testing their efficacy in the treatment and prevention of immune-mediated diseases.